Girl power ads and ends - Balin, Madeleine D.
Girl power ads and ends pertains to the seemingly feminist theme upheld in advertisement texts at present. In particular, it alludes to the liberal feminist aesthetic, which advocates an unfettered self-actualization process for women, generally reflected in recent Philippine television advertisements. Through the textual analysis of 72 such ads, insatiable and insurgent types of women were gleaned. The former embodied a woman in the process of furthering her already favorable situation while the latter projected a woman in the course of transcending her predicament. A survey of three residential areas affirmed the complementary regard of the viewing public of women as competent individuals in their own right. A focus interview with advertisers disclosed that the reason for the congruous fit of the substance of ads and the viewers' thinking is the fact that they, as ingenious yet truthful creators, base their ads from the audience, in particular, and the society, in general. Indeed, there exists a reflexive relationship among advertisers, viewers, and the social setting in the portrayal of women. None of these three elements is responsible for whatever gender ideology is predominant. Each influences and is, correspondingly, influenced by the others. Thus, TV ads are mere agents that augment viewers' ingrained definition of femininity. It is, therefore, endorsed by this study that matters of communication be deemed as a collaborative process. In other words, each of it elements must be considered as significant in the evolution of messages.